Side effects of long-term treatment with chloroquine for rheumatoid arthritis - a review of the literature - Sylwia Zdun; Klaudia Walczak; Weronika Gaweł; Zuzanna Wesołowska; Przemysław Jędruszczak; Natalia Grzywna; Sylwia Nemeczek; Konrad Merkisz; Jakub Grzybowski; Patrycja Walczak (Kazimierz Wielki University, 2022)
Background: Chloroquine is a 4-aminoquinoline derivative. Initially the substance was used as an antimalarial drug, but now chloroquine is also used to treat connective tissue diseases. It is a widely used drug in rheumatological diseases, especially in rheumatoid arthritis and systemic lupus erythematosus. A number of side effects have been reported in the public literature among patients using this drug. This article reviews side effects during long-term treatment of patients with rheumatoid arthritis. Materials and methods: A review of the literature available in the PubMed database was performed, using the key words: "Chloroquin" ; "Chloroquin rheumatoid" ; "Chloroquin toxicity" ; "Chloroquine" ; "Chloroquine rheumatoid" ; "Chloroquine toxicity". Results: Chloroquine is a quinine derivative, originally used in the prevention and treatment of malaria. It is now being successfully used to treat patients with certain connective tissue diseases, including rheumatoid arthritis. A number of publications have described various side effects of this drug. Serious and major problems arise from the drug's toxicity with long-term use, such as in the treatment of rheumatoid arthritis. Long-term use of the drug results in retinopathy and cardiotoxicity (conduction disturbances, cardiomyopathy). The available literature also mentions neuromyotoxicity which is rarely reported by patients. Conclusion: Long-term use of chloroquine carries serious side effects. The main complications of long-term use of the drug affect the visual, cardiovascular and nervous systems. The use of chloroquine in patients with rheumatoid arthritis should emphasize the need for accurate dosing and periodic cardiovascular, ophthalmologic and neurologic monitoring.